2015
DOI: 10.1007/s12665-015-4518-0
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of Zn(II) and Cu(II) by four Argentinean soils as affected by pH, oxides, organic matter and clay content

Abstract: Increasing heavy metal applications to agricultural soils in the form of phosphatic fertilizers and/or atmospheric deposition have led to extensive research on the chemistry of Zn and Cu in soils. Cu(II) and Zn(II) sorption onto different soil fractions of three Mollisols and one Entisol from the southwest of Buenos Aires Province, Argentina, was studied. Different variables affecting the sorption capacity such as pH, cation exchange capacity, specific surface area (SSA), type and amount of clay minerals prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…In all cases, crystallographically distinct T sites exert a minor influence, which is quite different from the scenario in zeolites. Quantity of negative charges is the foremost factor that differentiates the adsorption performances for different clay materials. In addition, for clay materials with variable charges, the adsorption of metal ions will be significantly altered by external conditions such pH, as supported by experimental observations that the enhanced adsorption of metal ions on clay materials at higher pH values is attributed to the increase of negative charges. , …”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…In all cases, crystallographically distinct T sites exert a minor influence, which is quite different from the scenario in zeolites. Quantity of negative charges is the foremost factor that differentiates the adsorption performances for different clay materials. In addition, for clay materials with variable charges, the adsorption of metal ions will be significantly altered by external conditions such pH, as supported by experimental observations that the enhanced adsorption of metal ions on clay materials at higher pH values is attributed to the increase of negative charges. , …”
Section: Resultsmentioning
confidence: 89%
“…In addition, for clay materials with variable charges, the adsorption of metal ions will be significantly altered by external conditions such pH, as supported by experimental observations that the enhanced adsorption of metal ions on clay materials at higher pH values is attributed to the increase of negative charges. 55,56 Adsorption can be also affected by the other factors but to a less extent. For different clay particles with close charge quantities, the adsorption performances of metal ions will not differ substantially, and structural alterations may be the primary factor (Figure 10).…”
Section: Double Substitutions In Mmtmentioning
confidence: 99%
“…Harter stated that SOM is an important factor in affecting sorption of heavy metal ions by soil. Removal of organic matter in soil dramatically decreased the sorption of heavy metal ions . Yu reported that the contribution of organic matter to the total negative surface charges of the paddy soils (derived from red soils) was 5–42% with an average of 21%.…”
Section: Discussionmentioning
confidence: 99%
“…In that sense, sorption on the surface of CaCO 3 , coprecipitation with carbonates, and formation of calcium zincate all reduce the amount of soil Zn extracted by DTPA in calcareous soils (Baruah, 2018). High carbonate content also increases soil pH, which is a driving factor of Zn availability, because the solubility of Zn minerals and the Zn desorption from clays and oxides decreases with increasing soil alkalinity (Catlett et al, 2002;Fernández et al, 2015).…”
Section: Resultsmentioning
confidence: 99%